Hydrogen accumulation and distribution in pipeline steel in intensified corrosion conditions - Titov A. I. Anatoly Ivanovich; Lun-Fu A. V. Aleksandr Viktorovich; Gayvoronskiy A. V. Aleksandr Viktorovich; Bubenchikov M. A. Mikhail Alekseevich; Bubenchikov A. M. Aleksey Mikhaylovich; Lider A. M. Andrey Markovich; Syrtanov M. S. Maksim Sergeevich; Kudiyarov V. N. Victor Nikolaevich (2019, 2019)
Title screen